Renin-Angiotensin System Inhibition Improves Lipid Profile in Patients with Chronic Kidney Disease - Salamah, Ola Zarreif; Zrieki, Afraa; Said, Hussein (Journal of medical and pharmaceutical sciences, 2023)
The aim of this study was to evaluate whether the blockade of renin-angiotensin system (RAS), achieved by angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II receptor blockers (ARBs), could affect the plasma lipid profile in chronic kidney disease (CKD) patients. Ninety-four hypertensive patients with CKD (stage 3-5) were enrolled. Forty-nine patients were treated with either ACEIs or ARBs daily for 6 months, and forty-five patients were treated with other antihypertensive agents (calcium channel blockers (amlodipine), b blockers, diuretics) as positive control group. Creatinine, estimated glomerular filtration rate (eGFR), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglyceride (TG) levels measurements were performed before and after the six-month treatment. An improvement in serum lipids levels in hypertensive patients with CKD resulted from RAS blocked therapy and other antihypertensive agents. Both treatment groups significantly decreased total cholesterol (TC), by 7.77% in ACEIs/ARBs group (p≤0.01) and 6.42% in other antihypertensive group (p≤0.05). In CKD patients treated with ACEIs/ARBs, levels of TG (3.29%), and LDL-C (3.15%) dropped more than with other antihypertensive medications (2.12%, and 1.19% respectively). RAS blocked therapy significantly increased HDL-C levels in CKD patients by 5.94% (p≤0.05). The results indicate that RAS blockade therapy with ACEIs or ARB positively affects lipid profile, which may improve the cardiovascular risks caused by CKD.